Imvotho: Umz'omkhulu Reclamation of Xhosa people's narrative on their relationship with water - Liwani, Yonela (School of Architecture, Planning and Geomatics, 2021)
This thesis confronts beliefs and perceptions, enforced over time, about the relationship Xhosa people have to water. Unpacking these assists in reclaiming the narrative origins of assumed myths about indigenous cultural beliefs and associations with nature and allows undocumented cultural narratives that are slowly vanishing to be recorded. The fragmented and vanishing narratives impact on the loss of cultural identity of black people. This fragmentation is felt acutely on the Cape Flats where postcolonial migration from the rural Eastern Cape to urban centres has severed the spiritual and emotional relationships with nature, particularly water. Khayelitsha is used as a case study site to reconnect people to their cultural narratives. The site has a highly polluted storm water attenuation pond in the middle of an informal settlement. The site selection was mostly informed by its direct link to the Xhosa people who have migrated from the Eastern Cape, accessibility for the people that the study is about and its inclusion of the environmental issues that exist on the site that further shift water associations and perceptions of the relationship Xhosa people have with water. This dissertation aims to uncover and examine the indigenous cultural systems that functioned in the rural spaces in Eastern Cape settlements, namely eNgcobo. Studying the landforms of water bodies, especially active water spaces and the systemic activities and human roles that occurred within the landforms, seeks to reconcile a urban language that allows for a healthy cultural connection to this natural system. Additionally, by understanding true cultural relationships that exist between people and natural systems within the traditional rural context it will provide design cues to apply in urban areas that allows urban populations to reconnect with their cultural identity and heal the negative perceptions towards water.